Analysis of Work of Uzbek Translators - Gulnoza Saydaliyeva Djambulovna (Journal of Learning on History and Social Sciences, 2024)
This article provides information about Uzbek translators who have given at least practical guidance to one of the most difficult and demanding arts - the art of literary translation, and emphasized that it is necessary to lay the fundamental foundations. And in the 20th century, fundamental research on translation studies came from prominent Central Asians, Western Europeans, and many scholars from the then sister republics, which are now newly independent states.